Principle-Based Concept Analysis Methodology Using a Phased Approach With Quality Criteria - Stephanie Smith (SAGE Publishing, 2021)
The study aimed to provide a detailed description of a process to conduct a phased principle-based concept analysis and to introduce quality criteria assessment for a phased principle-based concept analysis. Concept analysis explores how a concept is described, used and measured in the literature. This conceptual understanding is important to guide translational research to direct the development of evidence-based practice. The principle-based concept analysis is one approach of concept analysis used in published work, but the literature is lacking in articles clearly describing how to conduct it in practice. This article provides a methodology utilising a phased approach and by advancing on previous work; this approach includes a combination of a systematic search, quality criteria and qualitative analysis with principle-based concept analysis. Quality criteria for a phased principle-based concept analysis is introduced to critically assess articles against the four principles: epistemology, pragmatic, linguistic and logical. These improvements to the methodology promote transparency, rigour and replicability. This comprehensive systematic approach will aid future phased principle-based concept analyses and enable future comparisons of concept development, advancement and related concepts to improve the evidence base.